Regulatory T Cell Suppressive Activity Predicts Disease Relapse During Disease-Modifying Anti-rheumatic Drug Dose Reduction in Rheumatoid Arthritis: A Prospective Cohort Study - Kanjana, Korawit; Chevaisrakul, Parawee; Matangkasombut, Ponpan; Paisooksantivatana, Karan; Lumjiaktase, Putthapoom (Frontiers in Medicine, 2020)
When the dose of conventional disease-modifying anti-rheumatic drugs (cDMARDs) is tapered in rheumatoid arthritis (RA) patients who achieve sustained remission, biomarkers for predicting disease relapse may be needed. A prospective, unblinded cohort study was conducted in nine RA patients with remission. Peripheral blood samples were collected at baseline and at 6, 12 and 24 weeks after cDMARD dose reduction (dose of combination regimens reduced to 50%) to determine the number of regulatory Foxp3+T cells (Tregs) and other T cell subpopulations as well as Treg suppressive activity. Additionally, plasma levels of 14 cytokines at each time-point were measured via flow cytometry. Univariate and multivariate analyses were performed to identify the factor(s) associated with RA relapse during the observational period. In univariate analysis, Treg suppression and DAS28 and VAS scores were associated with RA relapse after cDMARD dose tapering. However, in multivariate analysis, only Treg suppressive activity (<42%) was found to be an independent factor associated with RA relapse after cDMARD dose reduction to 50%. Of all patients who had ≥42% Treg suppressive activity during cDMAD reduction, three-fourth patients remained in the remission stage for 24 weeks. Treg suppressive activity (<42%) in RA patients with remission could be a potential biomarker for predicting RA relapse after cDMARD dose reduction, especially over a short-term period (24 weeks).